In situ microbial fuel cell-based biosensor for organic carbon - Peixoto, L. (2011)
The biological oxygen demand (BOD) may be the most used test to assess the amount of pollutant organic matter in water; however, it is time and labor consuming, and is done ex-situ. A BOD biosensor based on the microbial fuel cell principle was tested for online and in situ monitoring of biodegradable organic content of domestic wastewater. A stable current density of 282±23 mA/m2 was obtained with domestic wastewater containing a BOD5 of 317±15 mg O2/L at 22±2 °C, 1.53±0.04 mS/cm and pH 6.9±0.1. The current density showed a linear relationship with BOD5 concentration ranging from 17±0.5 mg O2/L to 78±7.6 mg O2/L. The current generation from the BOD biosensor was dependent on the measurement conditions such as temperature, conductivity, and pH. Thus, a correction factor should be applied to measurements done under different environmental conditions from the ones used in the calibration. These results provide useful information for the development of a biosensor for real-time in situ monitoring of wastewater quality.